Comparative Toxicity Analysis Ethanol and Decoction Extracts of Curry Leaf (Murraya koenigii) Using Brine Shrimp Lethality Test - Husna, Fauzul; Zulkarnain, Zulkarnain; Nasywa, Ghina (Universitas Airlangga, 2025)
Curry leaves (Murraya koenigii) are used in traditional medicine; however, their toxicity and anticancer properties remain largely unexplored. This study assessed the toxicity of ethanol and decoction extracts of curry leaves using a Brine Shrimp Lethality Test (BSLT). Curry leaves were collected, dried, and extracted with 96% ethanol using the decoction method. Artemia salina larvae were exposed to extract concentrations (62.5, 125, 250, 500, and 1000 ppm) for 24 h. The lethal concentration 50 (LC50) values were determined by probit analysis. The ethanol extract showed toxicity with an LC50 of 263 ppm, whereas the decoction extract was non-toxic with an LC50 of 6,174 ppm. The ethanol extract had a higher mortality rate (93.3%) than the decoction extract (26.6%). The differential toxicity was due to the solvents and extraction techniques used. Ethanol extracts bioactive compounds, including toxic elements. The high temperature in the decoction process may break down heat-sensitive toxic compounds. This study concluded that the ethanol extract of curry leaves exhibited a more potent toxic effect than the decoction extract, warranting further research to identify toxic compounds with anticancer properties.